Search for a way to improve the serum albumin binding function and the functional state of the liver when hypertension combined with non-alcoholic fatty liver disease - Dzordzo, Yurii; Andreychyn, Serhiy (Journal of Education, Health and Sport, 2022)
Recently, there has been a significant increase in interest in research on hypertension (HT), primarily due to its high prevalence. The interest in studying this problem is also exacerbated by the often insufficient effectiveness of existing treatments. The effect of concomitant pathologies on HT, in particular non-alcoholic fatty liver disease (NAFLD), remains poorly understood. The aim of the study – to evaluate the changes in the serum albumin binding function (SABF) and its relationship with the biochemical parameters of the blood when HT and HT combined with NAFLD and to suggest ways of medical correction of the detected disorders. Material and methods. 76 individuals with stage 2 HT with degree 2–3 arterial hypertension were examined. They were divided into two groups. Group 1 included 28 patients with HT without concomitant diseases who received basic hypertension therapy, and group 2 included patients with concomitant NAFLD. The latter in turn was divided into two subgroups: 2a – 27 patients who in addition to basic HT therapy received additional Antral hepatoprotector 200 mg three times a day for 2 months, and 2b – 21 patients who received only basic HT therapy. All of them underwent a standard clinical examination, as well as SABF, protein fractions, and liver function indicators. The comparison group consisted of 25 healthy individuals, comparable in age and sex. Results and Discussion. Patients in group 1 showed moderate changes in the functional state of the liver, but they did not exceed the norm, patients in group 2 – a significant decrease in SABF, as well as protein metabolism (decrease in total protein, albumin, albumin-globulin ratio and increase globulins) and liver function (increased activity of aspartate aminotransferase, alanine aminotransferase, gamma-glutamyltranspeptidase, thymol levels, alkaline phosphatase and total bilirubin). After treatment, the majority of patients in subgroup 2 had a statistically significant increase in SABF and a quantitative improvement in protein fractions and functional state of the liver. In subgroup 2-b, where hepatoprotective treatment was not performed, significant changes in most indicators did not occur. The results may be related to the positive effect of the drug on the liver, which leads to improved functional status of hepatocytes and their protein-synthesizing ability. In subgroup 2 b, where hepatoprotective treatment was not performed, significant changes in most indicators did not occur. The results may be related to the positive effect of the drug on the liver leading to improved functional status of hepatocytes and their protein-synthesizing ability. Conclusions. Changes of the functional state of the liver are observed when HT without concomitant pathology. HT with NAFLD is accompanied by a significant decrease in SABF, changes in protein metabolism and the functional state of the liver. Prescribing Antral to such patients helps to increase SABF, normalize protein metabolism and improve the functional state of the liver.